2019
DOI: 10.17951/c.2018.73.1.19-30
|View full text |Cite
|
Sign up to set email alerts
|

Assessing accuracy of barley yield forecasting with integration of climate variables and support vector regression

Abstract: <p>Investigations of the relation between crop yield and climate variables are crucial for agricultural studies and decision making related to crop monitoring. Multiple linear regression (MLR) and support vector regression (SVR) are used to identify and model the impact of climate variables on barley yield. The climate variables of 36 years (1982–2017) are gathered from three provinces of Iran with different climate: Yazd (arid), Zanjan (semi-arid), Gilan (very humid). Air temperature by high correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The model performance results from this study are similar to those from the literature [5,14,[52][53][54]: (a) the performance of the SVR-based model was better than the traditional linear model (i.e., linear regression model), and (b) the models must frequently be retrained to enhance the prediction performance when the range of the test dataset exceeds the training dataset, especially if the dataset is a data stream or time series. Therefore, the MBO/SVR model can be successfully and suitably applied to agricultural output prediction issues because it demonstrates the best performance, especially for predicting long-term agricultural output without retraining the prediction model.…”
Section: Discussionsupporting
confidence: 75%
“…The model performance results from this study are similar to those from the literature [5,14,[52][53][54]: (a) the performance of the SVR-based model was better than the traditional linear model (i.e., linear regression model), and (b) the models must frequently be retrained to enhance the prediction performance when the range of the test dataset exceeds the training dataset, especially if the dataset is a data stream or time series. Therefore, the MBO/SVR model can be successfully and suitably applied to agricultural output prediction issues because it demonstrates the best performance, especially for predicting long-term agricultural output without retraining the prediction model.…”
Section: Discussionsupporting
confidence: 75%
“…In our study the percentage deviation of estimated yield by observed yield done at tillering, flowering and grain filling stage by the SVR model was between 1.03 to 17.54 %. Parviz (2018) observed that the minimum correlation coefficient between the observed and simulated yield for barley was found in the Gilan province using a support vector machine. In our study LASSO modal performed well for yield prediction done at tillering, flowering and grain filling stages.…”
Section: Percentage Deviation Of Predicted Yield Done At Different St...mentioning
confidence: 98%
“…Parviz [23] used two methods, SVR and MLR, to predict barley yield in three Iranian provinces with arid, semi-arid, and humid climates. The results of this study showed that SVR is a better method for making a prediction for the considered 36-year period.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Sharifi [23] investigated prediction of barley yield in Iran, which is one of the rainfed crops that can be grown in the region, NDVI, EVI, temperature and evaporation indicators were considered. Although, other factors such as soil moisture and rainfall can be considered in the growth of rain-fed barley.…”
Section: Review Of Literaturementioning
confidence: 99%